180k views
3 votes
Please help me I do not understand ​

Please help me I do not understand ​-example-1
User Groot
by
5.6k points

1 Answer

5 votes

Answer:


b=-(-mx-2x+2m-60)/(x);\quad \:x\\e \:0

Explanation:

Given the expression


\left(x-2\right)\left(x-m\right)=x^2-bx+60

switch sides


x^2-bx+60=\left(x-2\right)\left(x-m\right)

subtract x² from both sides


x^2-bx+60-x^2=\left(x-2\right)\left(x-m\right)-x^2

simplify


-bx+60=-mx-2x+2m

subtract 60 from both sides


-bx+60-60=-mx-2x+2m-60

simplify


-bx=-mx-2x+2m-60

subtract x from both sides; x≠0


(-bx)/(-x)=-(mx)/(-x)-(2x)/(-x)+(2m)/(-x)-(60)/(-x);\quad \:x\\e \:0

simplify


b=-(-mx-2x+2m-60)/(x);\quad \:x\\e \:0

Thus,


b=-(-mx-2x+2m-60)/(x);\quad \:x\\e \:0

User Lorna
by
6.4k points